2022
DOI: 10.3390/toxins14040262
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Antiviral Properties of Alkaloids Isolated from Pancratium maritimum

Abstract: Ten Amaryllidaceae alkaloids (AAs) were isolated for the first time from Pancratium maritimum collected in Calabria region, Italy. They belong to different subgroups of this family and were identified as lycorine, which is the main alkaloid, 9-O-demethyllycorine, haemanthidine, haemanthamine, 11-hydroxyvittatine, homolycorine, pancracine, obliquine, tazettine and vittatine. Haemanthidine was isolated as a scalar mixture of two 6-epimers, as already known also for other 6-hydroxycrinine alkaloids, but for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
1
14
1
Order By: Relevance
“…Several studies demonstrated the antiviral effect of AAs against several types of viruses [ 18 , 19 , 20 , 21 , 22 , 23 , 36 , 37 , 38 ]. Here, the virus used to perform DENV GFP infections corresponded to dengue serotype 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies demonstrated the antiviral effect of AAs against several types of viruses [ 18 , 19 , 20 , 21 , 22 , 23 , 36 , 37 , 38 ]. Here, the virus used to perform DENV GFP infections corresponded to dengue serotype 2.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the virus used to perform DENV GFP infections corresponded to dengue serotype 2. Recently, we also uncovered that the Amaryllidaceae alkaloids haemanthamine, pancracine, and haemanthidine, which were isolated from Pancratium maritimum , inhibited DENV-2 infection [ 23 ]. This study added to the growing evidence that AA structures could be optimized to develop potent inhibitors against this potentially fatal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lycorine and haemanthidine ( 1 and 59 ) showed cytotoxic activity on Hacat cells and A431 and AGS cancer cells, while pancracine ( 41 ) exhibited selective cytotoxicity against A431 cells [ 104 ]. Alkaloids 2 , 5 , 41 and 59 also showed antiretroviral activity, inhibiting pseudotyped human immunodeficiency virus (HIV)−1 with EC 50 values of 25.3 and 18.5 µM, respectively [ 104 ]. In addition, all the alkaloids were able to avoid dengue virus (DENV) replication with EC 50 values ranging from 0.34 to73.59 µM at low non-cytotoxic concentrations (CC 50 ranged from 6.25 µM to >100 µM [ 104 ]).…”
Section: Alkaloids Isolated From Amaryllidacae Plants Collected In Me...mentioning
confidence: 99%
“…Among these there are alkaloids isolated from Amaryllidaceae and alkylamides [7,8], with the latter being a broad and expanding group found in at least 33 plant families [8]. Alkylamides and alkaloids have been observed to have antimicrobial [9][10][11][12][13][14], antiprotozoal [11,15], antiviral [16,17], insecticidal [18][19][20][21], nematocidal [22], cytotoxic [17], anticancer [23][24][25][26][27][28][29][30][31][32], acetylcholinesterase inhibition [27,28], and bioherbicidal activities [20,30]. Some plant extracts with potential herbicidal activity were also appropriately formulated in biopolymers [31,32].…”
Section: Introductionmentioning
confidence: 99%